PENDEKATAN METODA A CTIVITY BASED COSTING PADA PERENCANAAN HARGA POKOK PRODUKSI UNTUK MEMPEROLEH KEUNGGULAN BERSAING - Sumarsid . (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2011)
Ability to survive of an industry are very determined of ability to maintain the power of competitiveness. One ofpower competitiveness still significant is sale price. To gain the good sale price required efficiency and the accuracy of determination of the cost of good sold. In the determination of the cost of good sold required three of information Le: the cost of raw material, the cost of direct labor and overhead cost of production. Overhead cost is the component of cost it is difficult to control because there are can not be directly connected to cost object One way counting of overhead cost with the Activity Based Costing method. Activity Based Costing method most important with the activities in production process.